2014
DOI: 10.17557/tjfc.76502
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Long-Term Tillage Systems on Yield and Yield Component of Yellow and Narrow-Leaved Lupin

Abstract: A field experiment was conducted in the Wielkopolska region (52• 29' N, 16• 49' E, Poland) in Central Europe. The study was conducted over a 3-year period (2008, 2009, 2010) as a two-factorial desingn with four replications in the randomised plots The first factor consisted of lupin species (S): yellow lupin (YL) and narrow-leaved lupin (BL); the second factor was the adopted soil tillage system (TS): conventional tillage (CT), reduced tillage (RT) and no-tillage (NT). The following tillage systems were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…In the current study, as with earlier experiments [28], the soil tillage systems did not have a significant influence on number of seeds per plant pod, although the CT and RT systems led to a reduction in the number of pods and seeds per plant. Moreover, tillage system did not have an influence on seed yield of NL and yellow lupin, which amounted to approximately 1 t ha −1 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the current study, as with earlier experiments [28], the soil tillage systems did not have a significant influence on number of seeds per plant pod, although the CT and RT systems led to a reduction in the number of pods and seeds per plant. Moreover, tillage system did not have an influence on seed yield of NL and yellow lupin, which amounted to approximately 1 t ha −1 .…”
Section: Discussionsupporting
confidence: 87%
“…In the present experiment, the highest plant density was found in CT (75.4 m 2 ) and was significantly lower under RT (by 7.7%) and NT (by 24.8%). In the earlier study [28], the results were similar: the lowest plant density for yellow lupin (cv. Mister) and narrow-leaved lupin (cv.…”
Section: Discussionsupporting
confidence: 56%
“…Genotypes that were superior in one of yield components can be involve in breeding program such as line15 for pods plant -1 , Local23 for seeds plant -1 and Dijon2, Ismailia2, Line23 and Giza1 for seeds pod -1 and Ismailia2 for 100 seed weight. These results showed the importance of landraces in breeding program and this was in agreement with the results of Christiansen et al, (2000), Raza and Jornsgard (2005), Gonzalez-Andres et al,(2007), Annicchiarico et al, (2010), Faligowska and Szukała (2015). Interaction and mean of the two seasons haring the same case letter, for a parameter, do not differ significantly at P 0.05.…”
Section: Field Performancesupporting
confidence: 92%
“…White lupin is an N2 fixing legume and it can also play a role in enhancing soil fertility (Faluyi et al, 2000). Lupins are cultivated for seeds (Faligowska et al, 2015), ruminant feed, as a green manure and for human nutrition (Huyghe 1997;Faluyi et al, 2000). White lupin requires grain yield improvement to realize its potential as a high-protein grain crop (Annicchiarico et al, 2010); however, followed by narrow-leaved and yellow lupin, it was found to be suitable for animal feeding as well as the production of high-protein concentrates for further food processing and use in animal and human nutrition (Sujak et al, 2006).…”
Section: Introductionmentioning
confidence: 99%